A study on an exit interview process, influencing the withdrawal of a turnover decision: Semiconductor manufacturing plant cases - Jeon, HyangSook; Wang, EunJa (Korean Journal of Industrial and Organizational Psychology, 2014)
This study aims to explore the reasons why employees of semiconductor manufacturing plants make a turnover decision, and their experiences on the factors that influence the withdrawal of a turnover decision during an exit interview with one’s superior and a human resources department staff in charge. The total number of participants was twelve, and the data was collected by conducting an in-depth interview and analyzed by Consensual Qualitative Research (CQR) method. The study results showed that there were three determinants of making a turnover decision: personal reasons irrelevant to an organization, conflicts with one’s superior, colleagues and subordinates, and a stress due to uncontrollable tasks. Four major factors that influence one’s withdrawal of a turnover decision during an exit interview with one’s superior and a human resources staff in charge were found: the interviewer him or herself, interviewer’s interview skills and attitude, participants’s cognitive and emotional changes, and the problem solving. Following the making of a turnover decision and a withdrawal, the participants experienced the weakening of a self-concept and the changes to their perspectives on an organization. This study is meaningful in the following respects. The research aimed at the members of an organization who actually had a turnover decision, and examined the factors that influenced the withdrawal of a turnover decision through an exit interview process for the first time. This study could serve as the basis when introducing a workplace counseling system or a training program for counseling techniques within an organization or a company, whilst also contributing significantly to the development of interview, leadership and communication training programs for the managers carrying out employee interviews within an organization.